2011
DOI: 10.17221/379/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation and nitrogen fixation in interspecies grafts of soybean and common bean is controlled by isoflavonoid signal molecules translocated from shoot

Abstract: Identification of common signals of nodulation control among legume species will facilitate progress in enhancing symbiotic nitrogen fixation of legumes in sustainable agriculture system. Grafting experiments between soybean and common bean were carried out to evaluate whether a common shoot signals control the expression of hypernodulation among the tow species. Grafting of a hypernodulating soybean mutant NOD1-3 shoots to three cultivars of normally nodulating common bean roots resulted in hypernodulation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The major findings are: (1) complete absence of or very weak institutions, policy and budgetary support for biotechnology research and lack of its integration into wider agricultural and overall development objectives, (2) limited knowledge of inoculation responses of both promiscuous and specifically nodulating legume varieties as well as the other factors that inhibit BNF, hence a weak basis for decision-making on biotechnology issues, (3) limited capacity and lack of sustainable investment, (4) poorly developed marketing channels and infrastructure, and limited involvement of the private sector in the distribution of inoculants, and (5) limited farmer awareness about and access to (much more than price) inoculants. The lessons learned in-clude the need: (1) to increase investment in Rhizobium inoculation technology development, and strengthen policy and institutional support, (2) for public private partnership in the development, deployment and dissemination of BNF technologies, (3) to develop effective BNF dissemination strategies (including participatory approach) to reach farmers, and (4) for greater emphasis on capacity building along the BNF value chain. According to an FAO report, production of N fertilizer for 2007 was 130 million tons of N, and this should further increase in the coming years (FAO 2008).…”
Section: Importance Of Biological Nitrogen Fixation By Legumesmentioning
confidence: 99%
See 1 more Smart Citation
“…The major findings are: (1) complete absence of or very weak institutions, policy and budgetary support for biotechnology research and lack of its integration into wider agricultural and overall development objectives, (2) limited knowledge of inoculation responses of both promiscuous and specifically nodulating legume varieties as well as the other factors that inhibit BNF, hence a weak basis for decision-making on biotechnology issues, (3) limited capacity and lack of sustainable investment, (4) poorly developed marketing channels and infrastructure, and limited involvement of the private sector in the distribution of inoculants, and (5) limited farmer awareness about and access to (much more than price) inoculants. The lessons learned in-clude the need: (1) to increase investment in Rhizobium inoculation technology development, and strengthen policy and institutional support, (2) for public private partnership in the development, deployment and dissemination of BNF technologies, (3) to develop effective BNF dissemination strategies (including participatory approach) to reach farmers, and (4) for greater emphasis on capacity building along the BNF value chain. According to an FAO report, production of N fertilizer for 2007 was 130 million tons of N, and this should further increase in the coming years (FAO 2008).…”
Section: Importance Of Biological Nitrogen Fixation By Legumesmentioning
confidence: 99%
“…Low temperature inhibits inter-organismal signaling between the two symbiotic partners. It has been shown that low temperature inhibits the biosynthesis and rhizosecretion of plant to-bacteria signal molecules (for example genistein from soybean roots, which are necessary for the induction of the nod genes of B. japonicum (Zhang and Smith 1997;Abd-Alla 2001, 2011. Low temperature also inhibit the induction of bacterial nodulation genes (nod gene) required for the biosynthesis of bacteriato-plant signaling molecules, lipo-chitooligosaccarides (LCOs), the so-called Nod factors ).…”
Section: Rhizobium-legume Molecular Signalling Exchangementioning
confidence: 99%
“…Evidence exist that the introduction of exogenous nod gene inducers increases nodulation and N 2 fixation of some legume species. Pretreatment of B. japonicum with genistein increased nodulation and N 2 fixation of soybean and common bean (Zhang and Smith 1996;Abd-Alla 1999, 2011; and preinduction of R. leguminosarum with hesperetin and naringenin was found to stimulate nodulation and plant dry matter accumulation of pea and lentil plants (Begum et al 2001). Flavonoid inducers act in low concentrations and the pre-activation of rhizobia used as inoculants (biofertilizers) in undoubtedly economically justified (Hassan & Mathesius 2012).…”
Section: Effect Of Salinity Stress On Nod Gene Expressionmentioning
confidence: 99%
“…The early interaction between flavonoids and NodD regulatory protein activates nod gene transcription and the synthesis of Nod factor that initiates nodule primordium (Maj et al 2010;Abd-Alla 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The common bean ( Phaseolus vulgaris L.) is an important legume for global food security and is an essential staple crop for more than 400 million people. In addition, it plays an important role in sustainable agriculture by fixing atmospheric nitrogen (Abd‐Alla ). The common bean stands out for its high nutritional value, containing proteins, carbohydrates, fibre, vitamins and minerals such as iron, phosphorus, calcium and magnesium.…”
Section: Introductionmentioning
confidence: 99%